CORRELATIVE STUDY BETWEEN MALOCCLUSION SEVERITY LEVEL AND ORAL HYGIENE STATUS AMONG STUDENTS AT SMP LPP WAKAF FOUNDATION UNIVERSITAS MUSLIM INDONESIA IN 2017 - Rafika Counsul; Yustisia Puspitasari; Sarahfin Aslan (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Malocclusion is a dentofacial growth deviation that interferes with mastication, deglutination, speech and facial harmony. In Indonesia, the prevalence of malocclusion is constantly high (around 80%) which reached 90% among school-age adolescents in 1983 and 89% in 2006. Malocclusion condition, especially crowding, can generate plaque accumulation and calculus formation because of toothbrush inability to outreach interdental areas in crowded teeth. Aims: To determine the correlation between malocclusion severity level and oral hygiene status among class VII and VIII students at SMP LPP YW Universitas Muslim Indonesia Makassar in 2017. Methods: This study is an observational analytic study using cross-sectional design. Target population is class VII and VIII students at SMP LPP YW Universitas Muslim Indonesia Makassar. The data was collected using ICON and OHI-S assessment method. Statistical analysis was performed using Spearman test. Results: The results showed p value = 0.01 which means that there was a significant correlation between malocclusion severity level and oral hygiene status with r = 0.314. Conclusion: There is a significant correlation between malocclusion severity level and oral hygiene status among class VII and VIII students at SMP LPP YW Universitas Muslim Indonesia Makassar in 2017.